Building Master Trainers to Facilitate Sexual Violence Prevention: A Pilot Study in Ghana - Caitlin M. Choi; Michelle L. Munro-Kramer; Lindsay M. Cannon; Ruth Owusu-Antwi; Angela D. Akorsu; Sarah D. Rominski (Ubiquity Press, 2020)
Background: Sexual violence is a widespread human rights violation that affects women and girls throughout the world, with particularly high rates among college-age youth. In the United States, many universities have developed primary prevention education programs to comply with federal mandates; however, these programs are limited in sub-Saharan Africa. Objectives: The purpose of this pilot study is to describe and evaluate the training of peer facilitators for a sexual violence prevention program at two universities in Ghana; the University of Cape Coast and Kwame Nkrumah University of Science and Technology. Methods: A three-day "master trainer" training was held focusing on sexual violence, sexual health, bias, healthy relationships, and facilitation skills. Participants completed pre- and post-test evaluations on knowledge, attitudes, and skills related to the topics and participants from the University of Cape Coast also participated in a focus group about bias and self-care. Findings: Participants (n = 23) at both universities demonstrated significant changes in the domains of: self-care knowledge, sexual violence knowledge, rape myth acceptance, and facilitation skills. Conclusions: This study provides early evidence about training methods for primary prevention programs aimed at students on university campuses in sub-Saharan Africa. Further research is needed on peer-facilitation, training, and primary prevention programs related to sexual violence for university students in sub-Saharan Africa.